Global Database for Naturally Occurring Radionuclides Associated with Offshore Oil and Gas Production - Ziran Wei; Songjie He; Stephanie Sharuga; Kanchan Maiti (Data, 2025)
This study compiles a comprehensive dataset on the occurrence, distribution, and potential impacts of Naturally Occurring Radionuclides (NORMs) near offshore oil and gas platforms. It encompasses data, including activities (Bq/l) and exposure levels (Msv), derived from various environmental matrices. A particular emphasis is placed on petroleum products and waste, such as produced water, scales, and sludges. The dataset contributes to a better understanding of the distribution of NORM wastes in marine environments, informs future radiological safety standards, contributes to the formulation of regulatory policies, and facilitates the design of mitigation strategies. The information—literature and data from five continents over the past 70 years—has been carefully compiled and organized to support intuitive analysis, making it a valuable tool for policymakers and researchers.